Hydrogen refuelling station calibration with a traceable gravimetric standard. (August 2020) - Maury, R.; Auclercq, C.; Devilliers, C.; de Huu, M.; Büker, O.; MacDonald, M.
Abstract: Of all the alternatives to hydrocarbon fuels, hydrogen offers the greatest long-term potential to radically reduce the many problems inherent in fuel used for transportation. Hydrogen vehicles have zero tailpipe emissions and are very efficient. If the hydrogen is made from renewable sources, such as nuclear power or fossil sources with carbon emissions captured and sequestered, hydrogen use on a global scale would produce almost zero greenhouse gas emissions and greatly reduce air pollutant emissions.The aim of this work is to realise a traceability chain for hydrogen flow metering in the range typical for fuelling applications in a wide pressure range, with pressures up to 875 bar (for Hydrogen Refuelling Station - HRS with Nominal Working Pressure of 700 bar) and temperature changes from −40 °C (pre-cooling) to 85 °C (maximum allowed vehicle tank temperature) in accordance with the worldwide accepted standard SAE J2601. Several HRS have been tested in Europe (France, Netherlands and Germany) and the results show a good repeatability for all tests. This demonstrates that the testing equipment works well in real conditions. Depending on the installation configuration, some systematic errors have been detected and explained. Errors observed for Configuration 1 stations can be explained by pressure differences at the beginning and end of fueling, in the piping between the Coriolis Flow Meter (CFM) and the dispenser: the longer the distance, the bigger the errors. For Configuration 2, where this distance is very short, the error is negligible. Highlights: Uncertainty sources of a HRS show that depressurization must be taken into account. Location of the mass flow meter can influence the measuring hydrogen mass accuracy. On-site measurements with a gravimetric standard provide an efficient way to calibrating a measuring system from a HRS. The ambient conditions can highly affect the measurements stability of the gravimetric test bench (wind, ice on pipe).